The Seismicity of Ischia Island, Italy: An Integrated Earthquake Catalogue From 8th Century BC to 2019 and Its Statistical Properties - Selva, Jacopo; Azzaro, Raffaele; Taroni, Matteo; Tramelli, Anna; Alessio, Giuliana; Castellano, Mario; Ciuccarelli, Cecilia; Cubellis, Elena; Lo Bascio, Domenico; Porfido, Sabina; Ricciolino, Patrizia; Rovida, Andrea (Frontiers in Earth Science, 2021)
Ischia is a densely inhabited and touristic volcanic island located in the northern sector of the Gulf of Naples (Italy). In 2017, the Mw 3.9 Casamicciola earthquake occurred after more than one century of seismic quiescence characterized only by minor seismicity, which followed a century with three destructive earthquakes (in 1828, 1881, and 1883). These events, despite their moderate magnitude (Mw < 5.5), lead to dreadful effects on buildings and populations. Here, we review and systematically re-analyse all the available data on the historical and instrumental seismicity, to build an integrated earthquake catalogue for Ischia with a robust characterization of existing uncertainties. Supported by new or updated macroseismic datasets, we significantly enriched existing catalogues, as the Italian Parametric Earthquake Catalogue (CPTI15) that with this analysis passed from 13 to 107 earthquakes. We also extended back by 6 years the coverage of the instrumental catalogue, homogenizing the estimated seismic parameters. The obtained catalogue will not only represent a solid base for future local hazard quantifications, but also it provides the unique opportunity of characterizing the evolution of the Ischia seismicity over centuries. To this end, we analyse the spatial, temporal, and magnitude distributions of Ischia seismicity, revealing for example that, also in the present long-lasting period of volcanic quiescence, is significantly non-stationary and characterized by a b-value larger than 1.